Tinkering toward utopia : a century of public school reform - Tyack, David B. (Harvard University Press, 1995)
In this book, David Tyack and Larry Cuban explore some basic questions about the nature of educational reform. Why have Americans come to believe that schooling has regressed? Have educational reforms occurred in cycles, and if so, why? Why has it been so difficult to change the basic institutional patterns of schooling? What actually happened when reformers tried to "reinvent" schooling? Tyack and Cuban argue that the ahistorical nature of most current reform proposals magnifies defects and understates the difficulty of changing the system. Policy talk has alternated between lamentation and overconfidence. The authors suggest that reformers today need to focus on ways to help teachers improve instruction from the inside out instead of decreeing change by remote control, and that reformers must also keep in mind the democratic purposes that guide public education.